Clinicopathological implications of immunohistochemical expression of TBX21, CXCR3, GATA3, CCR4, and TCF1 in nodal follicular helper T-cell lymphoma and peripheral T-cell lymphoma, not otherwise specified - Bogyeong Han; Sojung Lim; Jeemin Yim; Young Keun Song; Jiwon Koh; Sehui Kim; Cheol Lee; Young A Kim; Yoon Kyung Jeon (Korean Society of Pathologists & the Korean Society for Cytopathology, 2024)
Background The classification of nodal peripheral T-cell lymphoma (PTCL) has evolved according to histology, cell-of-origin, and genetic alterations. However, the comprehensive expression pattern of follicular helper T-cell (Tfh) markers, T-cell factor-1 (TCF1), and Th1-and Th2-like molecules in nodal PTCL is unclear. Methods Eighty-two cases of nodal PTCL were classified into 53 angioimmunoblastic T-cell lymphomas (AITLs)/nodal T-follicular helper cell lymphoma (nTFHL)-AI, 18 PTCLs-Tfh/nTFHL-not otherwise specified (NOS), and 11 PTCLs-NOS according to the revised 4th/5th World Health Organization classifications. Immunohistochemistry for TCF1, TBX21, CXCR3, GATA3, and CCR4 was performed. Results TCF1 was highly expressed in up to 68% of patients with nTFHL but also in 44% of patients with PTCL-NOS (p > .05). CXCR3 expression was higher in AITLs than in non-AITLs (p = .035), whereas GATA3 expression was higher in non-AITL than in AITL (p = .007) and in PTCL-Tfh compared to AITL (p = .010). Of the cases, 70% of AITL, 44% of PTCLTfh/nTFHL-NOS, and 36% of PTCL-NOS were subclassified as the TBX21 subtype; and 15% of AITL, 38% of PTCL-Tfh/nTFHL-NOS, and 36% of PTCL-NOS were subclassified as the GATA3 subtype. The others were an unclassified subtype. CCR4 expression was associated with poor progression-free survival (PFS) in patients with PTCL-Tfh (p < .001) and nTFHL (p = .023). The GATA3 subtype showed poor overall survival in PTCL-NOS compared to TBX21 (p = .046) and tended to be associated with poor PFS in patients with non-AITL (p = .054). Conclusions The TBX21 subtype was more prevalent than the GATA3 subtype in AITL. The GATA3 subtype was associated with poor prognosis in patients with non-AITL and PTCL-NOS.